Candid Infringement: Unraveling the Paparazzi Culture and Copyright Laws in India - A Legal Perspective (Journal of Intellectual Property Rights (JIPR), 2025)
In the glitzy world of fame, where every click of the camera holds value, who truly owns a celebrity’s image, the photographer or the star? This paper delves into the high-stakes clash between paparazzi culture and copyright law in India, unraveling the legal maze that pits creative freedom against privacy rights. Through a meticulous analysis of the Indian Copyright Act, 1957 and landmark judgments, this research debunks the glaring gaps in legislation that leave both photographers and celebrities vulnerable. What happens when a paparazzi shot goes viral? Can a celebrity claim ownershipof their own likeness? And where  does "fair use" end and exploitation begin? The findings reveal an urgent need for reform from clearer licensing norms, co-authorship possibilities, to legal recognition of the economic worth embedded in celebrity images. By proposing amendments to the Indian Copyright Act, 1957, this paper charts a path toward a fairer, more balanced system that could better harmonize the interests of paparazzi and celebrities. In an era where a single snapshot can make or break reputations, this research is instrumental.